Vasopressinergic Neurocircuitry Regulating Social Attachment in a Monogamous Species - Tickerhoof, Maria C.; Smith, Adam S. (Frontiers in Endocrinology, 2017)
The prairie vole (Microtus ochrogaster) is a socially monogamous rodent species that forms a lasting connection between mates, known as a pair bond. The pair bond is primarily characterized by three distinct behaviors: partner preference, selective aggression, and biparental care of the young. The presence of these behaviors in the prairie vole and their absence in closely related non-monogamous species makes the prairie vole an important model of social relationships and facilitates the study of the neurobiological mechanisms of social affiliation and attachment. The nonapeptide arginine-vasopressin (AVP) is an important neuromodulator of social behavior, and has been implicated in the regulation of the pair bond-related behaviors of the prairie vole, through activation of the AVP receptor subtype 1a (AVPR1a). Modulation of AVPR1a activity in different regions of the prairie vole brain impacts pair bond behavior, suggesting a role of AVP in neurocircuitry responsible for the regulation of social attachment. This review will discuss findings that have suggested the role of AVP in regulation of the pair bond-related behaviors of the prairie vole, and the specific brain regions through which AVP acts to impact these unique behaviors.